2016
DOI: 10.1186/s40809-016-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion measurement in brain death with intravoxel incoherent motion imaging

Abstract: Background: The assessment of brain death can be challenging in critically ill patients, and cerebral perfusion quantification might give information on the brain tissue viability. Intravoxel incoherent motion perfusion imaging is a magnetic resonance imaging technique, which extracts perfusion information from a diffusion-weighted sequence, and provides local, microvascular perfusion assessment without contrast media injection. Methods: Diffusion weighted images were acquired with 16 b-values (0-900 s/mm 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In acute stroke in the brain, a significant decrease in f was measured in the infarct core compared with the contralateral hemisphere in three independent studies. 41,81,83 In addition, in two patients with cerebral brain death, lack of cerebral perfusion could be demonstrated with IVIM, 84 while the perfusion of the territory of the external carotid artery was retained, in accordance with findings with other modalities 85 and with IVIM in rats. 86 To our knowledge IVIM has not been applied in strokes in any other organs than the brain.…”
Section: Strokesupporting
confidence: 80%
“…In acute stroke in the brain, a significant decrease in f was measured in the infarct core compared with the contralateral hemisphere in three independent studies. 41,81,83 In addition, in two patients with cerebral brain death, lack of cerebral perfusion could be demonstrated with IVIM, 84 while the perfusion of the territory of the external carotid artery was retained, in accordance with findings with other modalities 85 and with IVIM in rats. 86 To our knowledge IVIM has not been applied in strokes in any other organs than the brain.…”
Section: Strokesupporting
confidence: 80%
“…A relatively large amount of experimental evidence consistent with the interpretation that the IVIM method can provide in vivo perfusion information has been collected in the last few years [ 2 ]. In particular, the IVIM method has been shown to be applicable in a broad range of brain clinical investigations [ 3 ], both in the context of hyperperfused lesions such as in high-grade glioma [ 4 12 ], and hypoperfused lesions such as strokes [ 13 16 ], vasospasm [ 17 ], cerebral lymphoma [ 18 ] and cerebral death [ 19 ]. In addition, the method has shown promise for the survival prognosis in high-grade brain glioma [ 20 , 21 ], in differentiating recurrent tumor from radiation necrosis for brain metastases treated with radiosurgery [ 22 ], and as a surrogate marker for the progression of cerebral small vessel disease [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively large amount of experimental evidence consistent with the interpretation that the IVIM method can provide in vivo perfusion information has been collected in the last few years (Christian Federau, 2017). In particular, the IVIM method has been shown to be applicable in a broad range of brain clinical investigations , both in the context of hyperperfused lesions such as in high-grade glioma (Bisdas, 2013;Catanese et al, 2018;Gielen et al, 2017;Keil et al, 2015;Shen et al, 2016;Togao et al, 2016;Wang et al, 2019;Zou et al, 2018), and hypoperfused lesions such as strokes (C. Christian Federau et al, 2019;Suo et al, 2016;Yao et al, 2016), vasospasm (Heit et al, 2018), cerebral lymphoma (Yamashita et al, 2016) and cerebral death (Christian Federau et al, 2016). In addition, the method has shown promises for the survival prognosis in high-grade brain glioma Puig et al, 2016), in differentiating recurrent tumour from radiation necrosis for brain metastases treated with radiosurgery (Detsky et al, 2017), and as a surrogate marker for the progression of cerebral small vessel disease (Sau May Wong et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IVIM imaging is very powerful because it not only provides the information of classic diffusion imaging accurately, but also extracts information about perfusion imaging. Several clinical and simulation studies have shown that IVIM imaging is a promising technique to diagnose abnormalities in brain, liver, kidney, breast, and prostate [5][6][7][8][9][10]. There is no need for exogenous contrast agent injection to extract IVIM perfusion information, which is the main limitation of classical perfusion MRI.…”
Section: Introductionmentioning
confidence: 99%